PENENTUAN POTENSI TABIR SURYA EKSTRAK KLIKA ANAK DARA (Croton oblongus Burm F.) - Haeria Haeria; Surya Ningsi; Israyani Israyani (Jurnal Farmasi UIN Alauddin Makassar, 2014)
A study concerning the determination of the potential sunscreen extract cortex anak dara (Croton oblongus Burm f.) UV-Vis spectrophotometry. This study aims to determine the SPF value, percent transmission erythema (% Te), and the percent transmission of pigmentation (% Tp) of the extract cortex anak dara (Croton oblongus Burm f.) with use spectrophotometer UV-Vis. Determination of potential sunscreen SPF value is determined based on the calculation of %Te and %Tp. The measurement results indicate that the SPF value of the extract with a concentration of 300 ppm = 2,991. Value of %Te = 22, 655%, and the value of %Tp = 26.837%. SPF value can be determined extract cortex anak dara (Croton oblongus Burm f.) at a concentration of 300 ppm has a minimum level of protection and sunscreen for the result value %Te and %Tp extract cortex anak dara (Croton oblongus Burm f.) is said to not be able to hold the skin to prevent redness / erythema, but can withstand pigmentation or darkening of the skin.